Cyclic behavior of reinforced concrete bridge bent retrofitted with buckling restrained braces. (15th July 2016) - Bazaez, Ramiro; Dusicka, Peter
Highlights: Large-scale experiments utilizing BRBs for the retrofit of RC bents are presented. Two BRBs are designed and retrofitted RC bents experimentally evaluated. A novel gusset plate detailing is used to connect the BRB to the concrete elements. Test results show the effectiveness of the retrofit technique. Abstract: The cyclic behavior of a deficient reinforced concrete bridge bent retrofitted using buckling restrained braces (BRBs) was experimentally evaluated using large scale experiments and quasi-static cyclic loading that reflected subduction zone earthquake demands. The retrofitted reinforced concrete bent specimen consisted of two circular cross section columns, a rectangular cap beam and a buckling restrained brace in a diagonal configuration. The brace was secured to the bent using steel gusset plates and post-installed adhesive anchors. The retrofitted bent was designed to perform elastically or with minor damage under different seismic hazards design levels. Two BRB designs were considered in an effort to assess the influence of the BRB design on the overall bent performance. The data from these large-scale experiments were analyzed considering bent hysteretic response, observed damage, component curvatures, internal member loads, as well as the overall stiffness and energy dissipation characteristics. The results successfully demonstrated the effectiveness of utilizing buckling restrained braces for achieving high displacement ductility of the retrofitted structure, while also controlling the damage of the existing vulnerable reinforced concrete bent. No damage was observed in the connection regions of the brace throughout the loading history, leaving the potential for rapid replaceability of the sacrificial BRB element.